Synchronization Of the RTRW Utilization Program to The RPJMD and RKPD of North Lampung District In 2020-2024 - Runiawan, Aken Andha; Endaryanto, Teguh; Yuliawan, Dedy (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
North Lampung Regency currently has a North Lampung Regency RTRW for 2014-2034, apart from that, North Lampung Regency has also prepared a medium-term development plan in the form of an RPJMD document and an annual short-term one in the form of an RKPD document. The mandate of Law Number 26 of 2007 concerning Spatial Planning as amended by Law Number 6 of 2023 concerning the Determination of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law states that spatial planning plans must be able to act as direction. regional development. Synchronization of spatial plans with regional development plans ensures the implementation of regional development well. However, synchronizing space utilization programs in regional spatial plans with development plans has problems in North Lampung Regency. Therefore, the aim of this research is to evaluate the synchronization of the North Lampung Regency RTRW medium-term space utilization program with the North Lampung Regency RPJMD in 2020-2024 and evaluate the synchronization of the North Lampung Regency RTRW short-term space utilization program with the North Lampung Regency RKPD in 2020-2024. The research method uses quantitative descriptive analysis with secondary data from planning documents in the North Lampung Regency Government. The research results show that the synchronization of the medium-term space utilization program (RTRW-RPJMD) is still not optimal, with low levels of synchronization dominating. This is caused by a lack of socialization and involvement of implementing agencies in the preparation of spatial planning and development documents. Furthermore, at the short-term level (RTRW-RKPD), the level of synchronization is also relatively low. Several factors that are obstacles include inadequate planning, budget limitations, lack of community proposals, land availability, and the impact of the Covid-19 pandemic.